PENDAMPINGAN PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) PADA SMK NEGERI 3 BATURAJA SUMATERA SELATAN - Yunita Trimarsiah; Dian Sri Agustina; Fatimah Kesuma Astuti; Satria Novari; Taufik Sobri (CV. Denasya Smart Publisher, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced various sectors, including education. Vocational high schools (SMK) are required to adapt to technological advancements to prepare graduates with relevant competencies for the industrial world. However, the utilization of AI in learning activities at SMK Negeri 3 Baturaja is still limited due to a lack of understanding and skills among teachers and students. Therefore, this community service program aims to provide assistance in the utilization of Artificial Intelligence to support learning processes and improve digital literacy at SMK Negeri 3 Baturaja. The method used in this program includes needs analysis, training sessions, hands-on practice, and mentoring. The activities were conducted through workshops introducing basic AI concepts, demonstrations of AI-based educational tools, and guided practice in applying AI for learning, content creation, and task completion. The mentoring process ensured that participants were able to independently use AI applications responsibly and ethically. The results of this program indicate an increase in participants’ understanding of AI concepts and their ability to utilize AI tools to support teaching and learning activities. Teachers gained insights into integrating AI into instructional strategies, while students demonstrated improved motivation and creativity in completing learning tasks. In conclusion, AI utilization assistance effectively enhances digital competencies and supports innovative learning at SMK Negeri 3 Baturaja. Continuous mentoring and policy support are recommended to ensure sustainable implementation